Governing authorities in the same boat and a tale of two schedules: Marius Nel v Hessequa Local Municipality (2015) (Commonwealth Journal of Local Governance, 2018)
This article responds to the tension inherent in the Constitution of the Republic of South Africa 1996 which lists ‘the environment’ proper as a function of national and provincial government. The authors discuss one of the arguments raised in the recently decided case of Marius Nel and Others v Hessequa Local Municipality and Others (2015) with particular emphasis on what the court’s reasoning adds to the growing body of jurisprudence on local government’s authority to govern environmental matters and the need for cooperative environmental governance in the South African context. The article features an overview of the relevant facts and findings in the Hessequa case, followed by a discussion of the implications of the court’s judgment.